Effects of high and low maternal dietary sodium intake during pregnancy on the offsprings’ glomerular number in rats - Alias, Nurul Adilah; Wan Aziz, Wan Shamimi Amni; Che Mohamad, Che Anuar; Roslan, Rosazra; Aminuddin, Niferiti; Mohd Rashid, Muhammad Hakimi; Mohd Noor, Noriah (2015)
The blood pressure of the offspring of dams fed on low or high salt diet during pregnancy and lactation are higher than that of normal sodium dams. The mechanism of the programmed hypertension in the offspring has not been identified. The experiment aims at studying the effects of high and low maternal dietary sodium on their offsprings’ glomerular number in rats. Normotensive female rats were subjected to timed pregnancy. Pregnant rats were randomly divided into three groups and were fed either low-sodium diet (0.145% NaCl), normal diet (1.0%) or high-sodium diet (3.0% NaCl) during pregnancy. The newborn pups were sacrificed on day 1 postnatal. The kidneys were fixed in 4% paraformaldehyde and then processed to be embedded into paraffin wax. The kidneys were cut into 6µm and 10% of each kidney section was stained with Haematoxylin and Eosin. The antero-posterior (AP) thickness of the kidney was determined by multiplying the total number of sections of each kidney by the thickness of the section. The imaged of the sections were captured using LEICA DM750 microscope at X4 magnification. The glomeruli were counted using the point selection tool of LEICA LAS software. Our preliminary data showed a significant reduction in AP thickness and glomerular number of the offspring of dams receiving low and high salt diet as compared to normal salt diet as early as day 1 post-natal. There is also evidence of focal glomerular tuft retraction in the offspring of dam fed on high salt diet and haemorrhage were seen in the glomerular tuft and interstitium in the offspring of dam fed on high and low salt diet. There were no focal glomerular tuft retraction haemorrhage were seen in the offspring of dam fed on the normal salt diet. This suggest that dietary sodium intake affect nephrogenesis.